A decision-making method for consensus building applied to increase the chances of decision implementation in NPOs: the case of fundraising problem - Ziotti, Vanessa; Leoneti, Alexandre (Brazilian Journal of Operations & Production Management, 2021)
Goal: The present research aimed to demonstrate the use of a decision-making method based on game theory to support the resolution of a usual NPO’s management problem, which is the one of fundraising with different stakeholders’ preferences. Design / Methodology / Approach: The application of the method occurred within a NPO in the city of Ribeirão Preto, Brazil, and included: (i) a phase for structuring the problem in the form of a decision matrix; and (ii) a group decision phase for supporting the NPO’s director board in their group decision-making process. Results: The method predicted reasonably well the group decision, whose effects were demonstrated with a greater sense of justice. Two years after the decision made, the authors verified through a new visit to the NPO that the mix of the choice of the group and the method was indeed implemented. Limitations of the investigation: It should be noted that, given the sample size, the results achieved in this study should be corroborated by other studies that eventually replicate the procedures proposed here for verification of the main hypothesis Practical implications: However, it has been concluded that the use of a formal approach can contribute to the solution of the fundraising problem in NPOs environment, increasing the chances for decision’s implementation. Originality / Value: It is expected that the framework proposed can be used for other problems of group decision making in NPOs by the replication of the procedures presented in the paper.